Assessing the Merits and Effectiveness of Peer Teaching in Small Groups through the Employment of Different Learning Media - Shrivastava, Saurabh RamBihariLal; Shrivastava, Prateek Saurabh (Avicenna Journal of Medicine, 2023)
Background Peer teaching is a well-acknowledged method to facilitate teaching and learning among medical students. The objective of the study was to assess the merits and effectiveness of peer teaching in small groups using a student-centered approach through the employment of different learning media.Methods This was a cross-sectional descriptive study conducted among a group of 34 students from third professional year. Purposive sampling was used, wherein students were subdivided into five small groups. At the beginning, a pretest consisting of 10 multiple-choice questions was conducted on the topic “Epidemiology of Hypertension.” This topic was further subdivided into five subtopics, and five separate learning media (viz., video, PowerPoint, white board, chalk-and-talk, and chart) were allocated using the lottery method. Each group discussed the allotted topic and then presented their findings in the large group using the assigned learning media, while other groups gave feedback, and the best group was decided through multivoting. Posttest was administered and the results were compared with the pretest. Data entry was done in Microsoft Excel and analysis was done using SPSS 16. Descriptive statistics and paired t-test was used to compare the results in pretest and posttest at p level < 0.05.Results This innovative session of peer teaching featured 34 students, with a mean age of 22 ± 1.3 years. While carrying out the Kirkpatrick Level 1 evaluation, almost 90% students liked the role of the facilitator in stimulating interest in the topic. There was a mean average increase of 1.7 marks on comparing the scores of posttest with pretest (Kirkpatrick Level 2), and the reported difference was statistically significant. Joyful learning 24 (66.7%) and group discussion 23 (63.9%) emerged as the most liked aspects of the session.Conclusion In conclusion, peer teaching through learning media is an effective method as it promotes active learning, improves communication skills, and improves the academic performance of students. Peer teaching using different learning media proved to be quite effective in improvement of knowledge about epidemiology of hypertension, the pros and cons of different learning media, and encouraged creativity among students.
Keywords: peer teaching; learning media; student-centered; self-directed learning